Defining Spino-Pelvic Alignment Thresholds: Should Operative Goals in Adult Spinal Deformity Surgery Account for Age? - Lafage, Renaud; Schwab, Frank; Challier, Vincent; Henry, Jensen K; Gum, Jeffrey; Smith, Justin; Hostin, Richard; Shaffrey, Christopher; Kim, Han J; Ames, Christopher; Scheer, Justin; Klineberg, Eric; et al. (Spine (Philadelphia, Pa. 1976), 2016)
Retrospective review of prospective, multicenter database. The aim of the study was to determine age-specific spino-pelvic parameters, to extrapolate age-specific Oswestry Disability Index (ODI) values from published Short Form (SF)-36 Physical Component Score (PCS) data, and to propose age-specific realignment thresholds for adult spinal deformity (ASD). The Scoliosis Research Society-Schwab classification offers a framework for defining alignment in patients with ASD. Although age-specific changes in spinal alignment and patient-reported outcomes have been established in the literature, their relationship in the setting of ASD operative realignment has not been reported. ASD patients who received operative or nonoperative treatment were consecutively enrolled. Patients were stratified by age, consistent with published US-normative values (Norms) of the SF-36 PCS (<35, 35-44, 45-54, 55-64, 65-74, >75  y old). At baseline, relationships between between radiographic spino-pelvic parameters (lumbar-pelvic mismatch [PI-LL], pelvic tilt [PT], sagittal vertical axis [SVA], and T1 pelvic angle [TPA]), age, and PCS were established using linear regression analysis; normative PCS values were then used to establish age-specific targets. Correlation analysis with ODI and PCS was used to determine age-specific ideal alignment. Baseline analysis included 773 patients (53.7 y old, 54% operative, 83% female). There was a strong correlation between ODI and PCS (r = 0.814, P < 0.001), allowing for the extrapolation of US-normative ODI by age group. Linear regression analysis (all with r > 0.510, P < 0.001) combined with US-normative PCS values demonstrated that ideal spino-pelvic values increased with age, ranging from PT = 10.9 degrees, PI-LL = -10.5 degrees, and SVA = 4.1 mm for patients under 35 years to PT = 28.5 degrees, PI-LL = 16.7 degrees, and SVA = 78.1 mm for patients over 75 years. Clinically, older patients had greater compensation, more degenerative loss of lordosis, and were more pitched forward. This study demonstrated that sagittal spino-pelvic alignment varies with age. Thus, operative realignment targets should account for age, with younger patients requiring more rigorous alignment objectives.